2018
DOI: 10.1016/j.sdentj.2017.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Maxillary lateral incisor agenesis; a retrospective cross-sectional study

Abstract: The prevalence of missing maxillary lateral incisors in this study population was 1.91%) which was within the range reported in different populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 31 publications
0
18
1
1
Order By: Relevance
“…3 In a study done in Portuguese population prevalence of missing lateral incisors was found 1.3%. 2 The prevalence for missing maxillary lateral incisors was 1.91% in dental patients in study done by Arandi NZ et al 7 In the same study prevalenceof missing lateral incisors in males was 1.7% and in females was 2.1% which is in contrast with our study. 7 In a similar study done in orthodontic patients prevalence of missing lateral incisor was 9.42%.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…3 In a study done in Portuguese population prevalence of missing lateral incisors was found 1.3%. 2 The prevalence for missing maxillary lateral incisors was 1.91% in dental patients in study done by Arandi NZ et al 7 In the same study prevalenceof missing lateral incisors in males was 1.7% and in females was 2.1% which is in contrast with our study. 7 In a similar study done in orthodontic patients prevalence of missing lateral incisor was 9.42%.…”
Section: Discussioncontrasting
confidence: 84%
“…The mutations in genes responsible for tooth development are marked as PAX9 and MSX1. [6][7][8] There is remarkably little information in the literature on the prevalence of missing teeth and variation in shape of teeth in Nepalese context. The aim of the study was to investigate the prevalence of the congenitally missing lateral incisors and peg laterals in patients receiving orthodontic treatment.…”
Section: Introductionmentioning
confidence: 99%
“…It is very important on the part of clinicians to diagnose the type of teeth missing, the variations seen in relation to the gender affected, the etiology behind, either due to congenital absence of the related tooth buds or due to impactions and the type of skeletal base present and accordingly plan the treatment. [ 25 26 27 28 ] Arandi and Mustafa,[ 29 ] likewise, conducted a study on 2662 dental patients in Palestine who were evaluated for the prevalence of congenitally missing lateral incisors and found 1.91% of the subjects with unilateral agenesis accounting for up to 66.6% of the total cases. In addition, around 79% of the unilateral cases were on the left side while 21% were on the right side.…”
Section: Discussionmentioning
confidence: 99%
“…Maxillary lateral incisors agenesis may cause a variety of esthetic and functional problems; their absence may cause a diastema between the central incisors, spacing between permanent incisor and canine, mesial migration of canines, midline shift in case of a unilateral missing tooth. 5,9 The options available to the clinician are the possibility of space closure with mesial repositioning of canines, followed by teeth recontouring; or a combination of space opening and prosthetic replacement of the missing lateral tooth. 7 Missing teeth are significant enough reasons for extensive oral rehabilitation requiring orthodontic, restorative and prosthodontic procedures at the dental clinic, as various combinations of poor aesthetics and occlusal dysfunction are presented by the patients.…”
Section: Introductionmentioning
confidence: 99%
“…7 Missing teeth are significant enough reasons for extensive oral rehabilitation requiring orthodontic, restorative and prosthodontic procedures at the dental clinic, as various combinations of poor aesthetics and occlusal dysfunction are presented by the patients. 6,9 CASe RepORT This is a case of a 25-year-old female with maxillary lateral incisors agenesis, multiple maxillary anterior diastema, maxillary central incisors protrusion and mandibular dental midline shift to the left by 2 mm. Extraoral examination showed pleasing facial profile with competent lips.…”
Section: Introductionmentioning
confidence: 99%